Izobraževanje svojcev bolnikov po nezgodni možganski poškodbi - Povše, Maja (Rehabilitacija (Ljubljana), 2008)
Background: Relatives play an important role in the rehabilitation of patients so it is essential for the family to be acquainted with the consequences of traumatic brain injury as well as with its treatment. The aim of educational program is to improve quality of life of patients as well as of their relatives. Methods: Quality of the meetings was evaluated using the participant questionnaire, which was delivered after each meeting. Performers of the program made quality and success evaluation through informal interviews, observations and individual work with relatives. Results: Evaluation data collected showed that the design and delivery of the program were effective, and that the objectives were achieved. All planned meetings took place; 61% of the invited relatives attended them. Conclusions: Performance of such educational program demanded a lot of organizational arrangements, planning, and the program was constantly being adapted to participants. There was also the need to encourage the participants to take an active role during the meetings and during the rehabilitation process. Only due to intensive collaboration between the staff and the participants, the program could be successful and the aims could be achieved.
Keywords: možganske poškodbe; možgani; vocational rehabilitation; rehabilitacija; svojci; bolniki; education; izobraževanje